A review paper on cocomo model - pal, Gajender; kumar, Manish; barala, Kuldeep; ggn, Dce (IJRDO -Journal of Computer Science Engineering, 2015)
The COCOMO Model is well known as the currently predominate model for software cost estimation. It allows one to work from linguistic variables to estimate software project effort and schedule. This basis in linguistic variables encourages research of the COCOMO Model as a fuzzy system. As is known in fuzzy circles and is shown here, fuzzy arithmetic based on the popular fuzzy extension principle may produce unacceptable results under fuzzy multiplication. This makes fuzzy results of some computations too fuzzy to be useful. Nevertheless, in the case of software cost estimation using COCOMO, we find and show that this characteristic of fuzzy arithmetic may be used to advantage.